About Oirat Texts from the Handwritten Collection BM-574 from the Collection of P. B. Baldanzhapov - Deliash N. Muzraeva; Tsymzhit P. Vanchikova (Монголоведение)
Introduction. The collection of Oirat manuscripts by the famous Buryat scientist P. B. Baldanzhapov presents samples of Oirat texts collected by him during expeditions to Mongolia in the 1960s–1970s. Among these texts, along with hymns, praises of the deities of the Buddhist pantheon, sutras, fortune-telling books, descriptions of incense rituals, dharani texts (tarni) and texts against slander are presented. The purpose of the article is to present a description of the handwritten collection BM 574 in the Oirat language from the collection of P. B. Baldanzhapov, stored in the collections of the Central Historical Research Center of the IMBT SB RAS. Materials. The collection in question includes two texts: Xutuqtu biligiyin cāna kürüqsen tabün yoümiyin xürāngγüyin züreken kemēkü (“Holy [dharani], called ‘The Heart (Essence) of the Assembly of Five Mothers Who Have Achieved Transcendent Wisdom‘”) and Xutuqtu xara ama kele amurli ülün üyiledüqči kemēkü yeke külgüni sudur (“The Holy Mahayana Sutra, called “Pacifying Slander”). Results. Based on the analysis of the texts of the collection under consideration, their transliteration and translation into Russian in comparison with a number of published texts similar in topic, it was concluded that these texts are evidence of the existence of the Buddhist tradition among the Mongolian peoples, allowing one to get an idea of the thematic diversity of texts that have been circulating among believers. The texts considered shed light on the ritual side of Buddhist practice, aimed at eliminating various types of disasters and negative phenomena in the daily life of believers.